Mechanical properties of recycled kenaf/polyethylene terephthalate (PET) fiber reinforced polyoxymethylene (POM) hybrid composite - Dan-Mallam, Y. (2014)
Environmental concerns have attracted researchers to study the recycling of composite materials and thermoplastics due to the desire not to waste materials and reduce disposal of scraps that may eventually pollute the environment. The main objective of this article is to study the effect of recycling on the mechanical properties of kenaf fiber/PET reinforced POM hybrid composite. The virgin hybrid composite was produced by compression molding and later subjected to mechanical testing. The scraps obtained after the mechanical testing were shredded, granulated and subjected to compression molding to produce samples for mechanical testing. Tensile strength of 27 MPa was obtained and (after second recycling process) which is lower compared to 73.8 MPa obtained for the virgin hybrid composite. There was a significant increase in flexural modulus (4.7 GPa) compared to the virgin hybrid composite. The impact strength dropped to 4.3 J cm-1 as against 10.5 J cm-1 for the virgin hybrid composite. The results of thermal degradation showed about 80 weight loss for kenaf fiber between 300 and 350Â°C. The weight loss may be due to the degradation of cellulose and hemicellulose content of the fiber. The percentage water absorption of the recycled composite dropped by about 80 compared to the virgin hybrid composite. Â© 2013 Wiley Periodicals, Inc.